KEBIJAKAN ANTI PENCUCIAN UANG DAN PENCEGAHAN PENDANAAN TERORISME (APU/PPT) UNI EROPA TERHADAP HIGH-RISK THIRD COUNTRIES PERIODE 2015-2020 - Muhammad Taqaruby Narzain (2023)
FATF explained, that the situation of money laundering and terrorism financing is getting worse. As a result, the FATF urges states to take action against and encourages more aggressive efforts to combat money laundering and terrorism finacing practices. The EU is classified as a region that is quite serious and includes being active in combating money laundering practices, in 2015 the European Union adopted a modern regulatory framework which includes several regulations and directives, namely the EU's fourth directive, one of its policies is to apply policies to third countries, where the commission has obligations law to identify high-risk third countries that have strategy deficiencies in their AML/CFT regimes. Which policy sparked debate among numerous observers and the international community. Using descriptive qualitative research methodologies, this study seeks to look into EU policies toward high-risk third countries and uncover what motivates the EU to formulate these policies. This research uses the idea of the Adaptive Foreign Policy Model, as well as the concepts of Anti-Money Laundering and Combating Financing of Terrorism. The results of the research are that the policy is formed based on the principles of the EU's common foreign and security policy, which is designed to resolve conflicts and promote international understanding, based on diplomacy and respect for international rules. And the EU has also proven that this policy is not only detrimental to the related third countries but can also help the country's financial ecosystem and even internationally, although it is recognized that there are still many deficiencies from the methodology and implementation of these policies.